延长球磨机大齿轮使用寿命的实践与探讨 - 罗冬平; 黄初皓 (Jixie chuandong)
Base on the work experiences for many years, the author analyzed the problem in designing, manufacturing, using and maintaining of the gear of ball grinder and given the solution to these problems. The study of lengthering life expectancy of ball grinder’s gear is also included in the article, so it is worthy of being introduced to people who works in this field.